Virtual reality applications in education domain - Alfarsi G.; Mohd Yusof A.B. (Institute of Electrical and Electronics Engineers Inc., 2023)
Clinical research; Computer games; E-learning; Ergonomics; Industrial plants; Tourism industry; Cell phone; Computer generated; Education domain; Education sectors; Mechanical development; Mechanical plants; Virtual research; Virtual reality